Addendum to "the equivariant inverse problem in gauge field theories and the uniqueness of the Yang-Mills equations" [J. Math. Phys. 30, 2382 (1989)] - Noriega, R.J. (1990)
The main theorem of the previous paper is extended to the case where L = L(gij;Aiα;Ai α,j). References and notations are the same. © 1990 American Institute of Physics.